Teacher strike! : public education and the making of a new American political order - Shelton, Jon, 1978- (University of Illinois Press, 2017)
"A wave of teacher strikes in the 1960s and 1970s roiled urban communities. Jon Shelton illuminates how this tumultuous era helped shatter the liberal-labor coalition and opened the door to the neoliberal challenge at the heart of urban education today. Drawing on a wealth of research ranging from school board meetings to TV news reports, Shelton puts readers in the middle of fraught, intense strikes in Newark, St. Louis, and three other cities where these debates and shifting attitudes played out. He also demonstrates how the labor actions contributed to the growing public perception of unions as irrelevant or even detrimental to American prosperity. Foes of the labor movement, meanwhile, tapped into cultural and economic fears to undermine not just teacher unionism but the whole of liberalism"-- Provided by publisher.
Keywords: Strikes and lockouts -- Teachers -- United States -- History -- 20th century.; Teachers' unions -- United States -- History -- 20th century.; Public schools -- United States -- History -- 20th century.; Collective bargaining -- Teachers -- United States.; Labor movement -- United States -- History -- 20th century.; United States -- Politics and government -- 20th century.; Grèves et lock-out -- Enseignants -- États-Unis -- Histoire -- 20e siècle.; Écoles publiques -- États-Unis -- Histoire -- 20e siècle.; Négociations collectives -- Enseignants -- États-Unis.; Mouvement ouvrier -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Politique et gouvernement -- 20e siècle.; 1900 - 1999.; EDUCATION -- History.; POLITICAL SCIENCE -- Labor & Industrial Relations.; HISTORY -- United States -- 20th Century.; Collective bargaining -- Teachers; Labor movement; Politics and government; Public schools; Strikes and lockouts -- Teachers; Teachers' unions; United States; 1900-1999; History